Proliferative nodule in melanocytic nevi mimicking deep penetrating nevus - Ana Almodovar-Real; Alejandro Molina-Leyva; Jose Aneiros-Fernandez; Miguel Antonio Diaz-Martinez (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Proliferative nodules can occasionally arise on congenital and acquired melanocytic nevi. At first sight their clinical and pathologic features cause alert to both dermatologist and dermatopathologist. However, proliferative nodules are typically benign, regression is common and there is minimum risk of malignization. We present a new case of proliferative nodule in melanocytic nevi with features of deep penetrating nevus.